Evaluation of International Teak Provenance Trial Plot in North East Andhra Pradesh - Rao, P. S.; Venkaiah, K.; Murali, V.; Murti, S. S. N.; Sattar, S. A. (Indian Forester, 2001)
The International Provenance Trial Plot sponsored by FAO/DANIDA in collaboration with Andhra Pradesh Forest Department was established in 1973 at Maredumilli, North-East Andhra Pradesh, with 10 seed sources and one local seed source as control. The Analysis of Variance of data on 26 year old trees indicated non-significant differences among provenances for height, clear bole height, gbh, Crown scores while significant differences for survival rate, straightness and roundness of stem and health characteristics. Height and GBH growth of provenances ranged from 14.33 to 22.33 m and 42.80 to 69.78 cm and were comparable to site quality II/III reported for Teak in India. Among the indigenous seed sources ’Konni’ (Kerala) and exotic sources ’Ban Mae Pan’ (Thailand) were the best for all the parameters studied. Genetic Analysis showed low heritability (broad sense) estimates for the characters on height, gbh, health, crown and branching characters (below 30 per cent), while moderate to high estimates of heritability for straightness (32.85 per cent) and roundness of stems (39.46 per cent) and clear bole height (60.50 per cent) characters. It is suggested that selections could be made from superior trees of individual provenances in order to have a broad base for genetic improvement of Teak in Andhra Pradesh.